2010
DOI: 10.1261/rna.2160010
|View full text |Cite
|
Sign up to set email alerts
|

Subribosomal particle analysis reveals the stages of bacterial ribosome assembly at which rRNA nucleotides are modified

Abstract: Modified nucleosides of ribosomal RNA are synthesized during ribosome assembly. In bacteria, each modification is made by a specialized enzyme. In vitro studies have shown that some enzymes need the presence of ribosomal proteins while other enzymes can modify only protein-free rRNA. We have analyzed the addition of modified nucleosides to rRNA during ribosome assembly. Accumulation of incompletely assembled ribosomal particles (25S, 35S, and 45S) was induced by chloramphenicol or erythromycin in an exponentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
68
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 46 publications
11
68
0
Order By: Relevance
“…Nascent 23S rRNA seems to be the natural substrate for YhiR. This result is in agreement with an earlier study (Siibak and Remme 2010) indicating that modification of the 23S rRNA nucleotide A2030 occurs early in the 50S subunit assembly.…”
Section: Yhir Methylates 23s Rrna In Vitrosupporting
confidence: 93%
“…Nascent 23S rRNA seems to be the natural substrate for YhiR. This result is in agreement with an earlier study (Siibak and Remme 2010) indicating that modification of the 23S rRNA nucleotide A2030 occurs early in the 50S subunit assembly.…”
Section: Yhir Methylates 23s Rrna In Vitrosupporting
confidence: 93%
“…Given that most 50S subunits in cells are associated with 30S subunits at sufficient concentrations of Mg 2+ , it is reasonable to speculate that the physiological substrate for RlmE is not the 50S subunit, but rather the 45S precursor, because Um2552 in H92 of 23S rRNA is located on the interface side of the 50S subunit (24)(25)(26). Quantitative analyses of rRNA modifications by HPLC/MS have shown that the level of Um2552 surges during late steps of 50S assembly (32,33), and these results are consistent with our observations. To obtain insights into the function of an RNA modification responsible for a specific biological process, it is necessary to determine whether the RNA-modifying enzyme or the RNA modification itself plays a pivotal role in the process.…”
Section: Discussionmentioning
confidence: 99%
“…5). RluD is, according to current knowledge, the only pseudouridine synthase acting during late stages of ribosome assembly (Siibak and Remme 2010).…”
Section: Discussionmentioning
confidence: 99%